1995
DOI: 10.1063/1.871489
|View full text |Cite
|
Sign up to set email alerts
|

Helium transport and exhaust studies in enhanced confinement regimes in DIII-D

Abstract: Portions of this document may be illegible in electronic image products. lmages are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 15 publications
7
64
0
5
Order By: Relevance
“…The electron density (ne) profile is measured using multi-pulse Thomson scattering [29] The ion temperature (Ti) profile is determined from charge exchange recombination (CER) emission of carbon impurities [31]. The carbon density found from the CER emission also determines the average ion charge (ZeR) profile [32]. An array of foil bolometers is used to measure the radiated power (Prad) profile [33].…”
Section: Methodsmentioning
confidence: 99%
“…The electron density (ne) profile is measured using multi-pulse Thomson scattering [29] The ion temperature (Ti) profile is determined from charge exchange recombination (CER) emission of carbon impurities [31]. The carbon density found from the CER emission also determines the average ion charge (ZeR) profile [32]. An array of foil bolometers is used to measure the radiated power (Prad) profile [33].…”
Section: Methodsmentioning
confidence: 99%
“…This formula is seldom used for the evaluation of the transport coefficients because of the difficulty in measuring the total impurity ion density experimentally. Previous applications to impurity transport [14] used charge exchange recombination spectroscopy (CXRS) while in a recent work [15] the method has been applied to study electron transport in-between sawtooth crashes within the q = 1 surface. Other impurity transport studies (e.g.…”
Section: Determination Of the Impurity Transport Coefficientsmentioning
confidence: 99%
“…This allows determination of E r in the plasma core and understanding of its evolution when transport barriers develop [27,28]. In addition, helium transport studies based on this analysis demonstrated that helium exhaust in ELMing H-mode plasmas is sufficiently fast for helium ash removal in tokamak fusion reactors [32,33].…”
Section: A Charge Exchange Recombinationmentioning
confidence: 99%